An International Tribunal for the Use of Nuclear Weapons. Issue 1 (2nd January 2019) - Colangelo, Anthony J.; Hayes, Peter
ABSTRACT: Although offenses against international law have been proscribed at a certain level of generality, nobody hitherto has examined closely the scientific and ecological damages that would be imposed by nuclear strikes in relation to resulting possible law-of-war violations. To correct that information deficit and institutional shortfall, the first Part of this Article constructs a hortatory proposal for a tribunal for the use of nuclear weapons under international law. The second Part of the Article shows how such a tribunal statute would have a real-world effect on those charged with launching nuclear strikes and determining the legality of the strike orders. For the first time, through a series of interviews and electronic communications, we have gathered empirical and anecdotal information regarding the actual processes of launch instructions to lower level crewmembers and, in particular, those who refused the order – or "refuseniks". What emerges from these accounts is the startling reality that low-level crewmembers had little or no guidance on the legality of the strike under the laws of war but were told simply to trust their leadership. A tribunal statute geared specifically to the use of nuclear weapons would provide needed guidance and constitute solid legal grounds upon which to stand should those lower down in the chain of command find the order to launch a nuclear strike manifestly illegal under international law.